Legal Review of Application for Customary Land Rights Based on National Land Law Regulations - Endah Pertiwi (DE LEGA LATA: JURNAL ILMU HUKUM, 2022)
The definition of control over land is a concrete legal relationship (usually called "rights"), if it has been linked to certain land as the object and a certain person or legal entity as the subject or right holder. sons who are subject to customary law who do not have written evidence, are owned by local residents, often called customary land, for example, customary land rights, can be registered with the Confirmation of Conversion and Registration of Former Indonesian Rights to Land, this journal is a normative juridical research with the approach method of legislation. Invitation, case approach and conceptual approach, this study aims to analyze and explain the Process of Application for Customary Land Rights and Provisions Regarding Cancellation of Land Certificates. a Conversion that can be applied to the local Land Office with evidence possessed by the land authority. With the issuance of a certificate as strong evidence that can cause a dispute, then it can be canceled with provisions so that the land administration system is orderly and legal protection for anyone without being harmed. With so many rights to customary lands and other lands that do not have rights, it is hoped that the community and the government can collaborate well to create administrative order and avoid land disputes